ANTI PARTAI POLITIK ISLAM DALAM PEMIKIRAN NURCHOLIS MADJID - Shohibul Azizi (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2014)
In 1970, Nurcholish Madjid stated "Islam yes, islamic parties no" within his speech in Menteng Raya Jakarta in the moment of night meeting among the organization of youths, leaners, students, and scholars of moslem coming form HMI (Himpunan Mahasiswa Islam), GPI (Gerakan Pemuda Islam), PII (Pelajar Islam Indonesia) and Persami (Persatuan Sarjana Muslim Indonesia). He is not interested in islamic parties, since the leaders of the islamic parties existing in that time did not became the transmitters ofmoslem community's  aspiration any longer. Instead, they only struggled their parties and their own interests. Beside, they also were devided into different denominations who had no strong commitment to the struggle of moslem community. He asserts his standpoint that his commitment is merely to Islam, not to Islamic institution.